Plastic depolymerization using metal organic framework-based catalysts

By using a metal organic framework (MOF) catalyst to contact the plastic waste raw material during the plastic depolymerization process, the unpredictable catalyst activity in the prior art is solved, and efficient plastic depolymerization at lower temperatures is achieved, and the quality of the depolymerization product obtained is improved, which is suitable for use as a cracker raw material.

CN119855802APending Publication Date: 2025-04-18BASELL POLIOLEFINE ITALIA SRL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380065132.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-07
Filing Date
2023-10-05
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when plastic depolymerization is used by catalysts, catalyst activity exhibits unpredictable properties in complex plastic waste raw materials and is difficult to efficiently depolymerize at lower temperatures.

Method used

The metal organic framework (MOF) catalyst is used to contact the molten plastic waste raw materials within a temperature range of 280°C to 600°C to carry out the depolymerization reaction. The process includes mixing with plastic waste feedstock using 0.1 to 20 wt% MOF catalyst and performing pyrolytic depolymerization under anaerobic conditions.

Benefits of technology

It realizes efficient plastic depolymerization at lower temperatures, and the quality of the depolymerization product obtained is improved, suitable for use as a cracker raw material, and the amount of catalyst usage is controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005305362340000111
    Figure BDA0005305362340000111
  • Figure BDA0005305362340000121
    Figure BDA0005305362340000121
Patent Text Reader

Abstract

Described herein is a method of depolymerizing plastic waste using a MOF catalyst. The process provides a high quality liquid depolymerization product at high efficiency that can be used as a cracker feedstock.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a catalytic method for depolymerizing plastic feedstocks and to certain catalysts for depolymerization. More specifically, the present disclosure relates to a method for depolymerizing plastic feedstocks in the presence of a metal organic framework (MOF) catalyst. Background Art

[0002] Plastics are cheap and durable materials that can be used to make a variety of products used in a wide range of applications, causing the production of plastics to increase significantly over the past few decades. Due to the durability of the polymers involved in plastic production, more and more plastics are filling landfills and occupying natural habitats around the world, causing environmental problems. Even degradable and biodegradable plastics can last for decades, depending on local environmental factors such as ultraviolet light exposure levels, temperature, the presence of suitable microorganisms, and other factors.

[0003] Current plastic recycling mainly includes mechanical recycling and chemical recycling. Globally, mechanical recycling is the most commonly used method for new uses of plastics, through which plastics are mechanically transformed without changing their chemical structure, so they can be used to produce new materials. Typical mechanical recycling steps include collecting plastic waste; sorting plastic waste into different types of plastics and colors; packaging plastics by pressing or milling plastics; washing and drying the plastics; reprocessing plastics into pellets by bonding, extruding and cooling plastics; and finally obtaining recycled raw materials. This is the most widely used technology for polyolefins such as polyethylene (PE) and polypropylene (PP).

[0004] On the other hand, chemical recycling reprocesses plastics and changes their structure so that they can be used as raw materials for different industries or as basic input or raw materials for manufacturing new plastic products. Chemical recycling usually includes the following steps: collecting plastics, then heating the plastics to a temperature at which the polymers break down into small fragments. This method, also known as depolymerization, is a basic method in which plastic waste materials are converted into liquid fuels by thermal degradation (cracking) in the absence of oxygen. Plastic waste is usually first melted in a stainless steel chamber under an inert purge gas (e.g., nitrogen). The chamber then heats the molten material to a gaseous state, extracts it, and then condenses it in one or more condensers to obtain a hydrocarbon distillate comprising straight and branched aliphatic, cyclic aliphatic and aromatic hydrocarbons. The resulting mixture can then be used as a fuel or as a raw material for further thermal catalytic processes to obtain refined chemicals such as monomers that can be reintroduced into the plastic manufacturing cycle.

[0005] The step of converting the molten plastic mass into a gaseous stream can in principle be carried out solely by the action of heat (thermal depolymerization). However, it has been shown that the presence of a catalyst in this stage allows the depolymerization to be carried out at lower temperatures and more efficiently.

[0006] To this end, various catalysts have been proposed, usually based on depolymerization tests performed on virgin polymers or accurately pre-sorted recycled plastics consisting of essentially a single polymer. Under these "non-real" conditions, the catalyst may only show a slightly higher depolymerization activity relative to thermal depolymerization. However, these tests do not provide any information on how the catalyst will perform under real conditions, in particular on whether it will be affected by the poisoning effects of components from real plastic waste, and to what extent.

[0007] For example, zeolite-based catalysts show good depolymerization activity with virgin or separated recycled plastics, but when used with more complex plastic waste feedstocks, the catalyst activity suffers from significant attenuation. In fact, the performance of catalysts in the depolymerization of complex plastic waste feedstocks is unpredictable.

[0008] We have surprisingly found that metal organic framework catalysts, particularly when the plastic waste contains a polypropylene fraction, can give highly efficient pyrolysis products with improved quality for use as cracker feedstocks. Summary of the invention

[0009] Thus, one aspect of the present disclosure is a method for depolymerizing plastics comprising the steps of:

[0010] a) providing a molten plastic waste feedstock comprising at least recycled polypropylene, and;

[0011] b) subjecting the molten product obtained in (a) to a temperature ranging from 280° C. to 600° C. to obtain a depolymerized product;

[0012] The method is characterized by the fact that either or both of the molten product and the depolymerized product are contacted with a metal organic framework (MOF) catalyst.

[0013] Preferably, the amount of catalyst used ranges from 0.1 to 20 wt%, preferably 0.1 to 10 wt%, especially 0.1 to 5 wt%, relative to the total weight of the plastic waste feedstock and the catalyst.

[0014] Preferably, the plastic waste feedstock comprises a mixture of polyethylene and polypropylene in a weight ratio of 85:15 to 15:85, more preferably 80:20 to 20:80. The polyethylene may be one or more of high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE). The polypropylene (PP) may be a propylene homopolymer or a propylene copolymer with lower amounts of ethylene and / or butene. In addition, the feedstock may contain other polyolefins, such as polybutene. In a specific embodiment, the feedstock may also include a polymer mixture in combination with other materials, such as polystyrene (PS), ethyl-vinyl acetate copolymer (EVA), ethyl-vinyl alcohol copolymer (EVOH), polyvinyl chloride (PVC) or a mixture thereof. In a preferred embodiment, the feedstock consists of a mixture between polyethylene and polypropylene greater than 80 wt%, wherein the polypropylene accounts for greater than 50 wt% of the polypropylene / polyethylene mixture.

[0015] When the depolymerization process is carried out, care should be taken not to introduce an oxygen-containing atmosphere into the depolymerization system. The barrier to potential oxygen-containing atmospheres can be obtained with a series of means such as nitrogen blanketing and vacuum systems connected to the barrel of the extruder.

[0016] More specifically, the plastic feedstock mixture may be charged into the feed system of the depolymerization reactor through a hopper or two or more hoppers connected in parallel, and oxygen present in the atmosphere of the plastic waste material is substantially eliminated inside the hoppers.

[0017] The plastic feedstock can be fed directly into the depolymerization reactor for small scale testing. For larger scale, it is preferably fed to the depolymerization reactor via an extruder which in turn is fed with the plastic feedstock.

[0018] Preferably, the plastic waste is brought to a temperature at which substantially all of the material is melted and then fed into the depolymerization reactor. The extruder receives the plastic waste chopped into small pieces into a feed hopper, conveys the stream in a melting section, and heats the polymer by a combination of mixing energy and heat provided by a barrel heater. Typically, the melt temperature ranges from 250°C to 350°C.

[0019] Additives may optionally be incorporated into the melt with the aim of reducing the corrosiveness of the plastic waste or increasing the efficiency of the depolymerization.

[0020] During the extrusion process, one or more degassing steps can be foreseen to remove residual moisture present in the product.

[0021] Before feeding to the reactor, the molten stream may be filtered to remove solid impurities present in the plastic waste.

[0022] Any extrusion system may be used, such as a single screw extruder, a twin screw extruder, a twin screw extruder with a gear pump, or a combination thereof.

[0023] The mixing of the plastic waste feedstock and the catalyst can be carried out directly in the depolymerization reactor or in advance outside the reactor. When the mixing is carried out in the depolymerization reactor, the catalyst can be fed according to several options. The simplest one, preferably used in small-scale systems, is to pour the solid catalyst directly into the reactor under a nitrogen atmosphere. According to another option, the powdered catalyst can be fed into the reactor in the form of a liquid hydrocarbon slurry or a semi-solid slurry using a dedicated device.

[0024] Alternatively, mixing can be carried out outside the depolymerization reactor. In this case, several options are also possible. According to one of them, the catalyst is mixed with the plastic waste in a homogenizer device, and the mixture is then granulated. The pellets thus obtained (which can also contain other additives) can then be loaded into an extruder hopper, which is used to feed the polymerization reactor. Plastic waste and catalyst can also be loaded into the hopper respectively. In this case, mixing can be carried out in an extruder when the plastic waste is melted, and the plastic waste is subsequently fed into the depolymerization reactor.

[0025] The depolymerization reactor is preferably a stirred vessel operated at a temperature in the range of 300 to 550°C, more preferably 350 to 500°C, especially 350 to 450°C, having an inlet for the plastic feedstock and catalyst and an outlet for the gaseous depolymerization products.

[0026] In fact, as a result of the depolymerization process, a gaseous stream is produced which is sent to a condensation unit which liquefies the stream in whole or in part.

[0027] The condensation section receives the effluent gases from the depolymerization reactor and partially condenses them into an oil depolymerization product consisting essentially of hydrocarbons. A portion of the non-condensable gases can be collected and stored separately. The condensation section can consist of one or more stages, operating at different temperatures, under pressure or not, in order to recover the maximum amount of product depending on the volatility of the resulting formed compounds. Of course, the temperature range can vary depending on the operating pressure.

[0028] Preferably, the condensation section has at least two condensation stages, preferably operated at decreasing temperatures. As an example, in a small-scale plant, the first condensation stage is operated at a temperature range of 100 to 120° C., and the second condensation stage is operated at a temperature range of 2° C. to -20° C.:

[0029] It is also possible to subject the depolymerization products from the condensation stage to a second depolymerization stage carried out in the presence of the MOF already described. The second depolymerization stage can be carried out under conditions similar to those described for the previous depolymerization stage. When this arrangement is carried out, it is also preferred to recycle the catalyst and part of the liquid or semi-liquid material back to the first depolymerization reactor from which the solid residue is discharged. Analogously to the first depolymerization step, the gaseous discharge can be condensed in a subsequent condensation stage.

[0030] At the end of the process, preferably at least 80% by weight, and preferably 90% by weight, of the plastic starting material have been converted in the liquid or gaseous depolymerization product.

[0031] As mentioned above, the main use of the depolymerization product according to the present disclosure can be as a cracker feedstock. In this regard, it is preferred that a high yield of liquid depolymerization product is produced by the depolymerization process. In a preferred embodiment, the amount of liquid depolymerization product is greater than 60 wt % of the plastic waste feedstock, more preferably 65 to 85 wt %.

[0032] Furthermore, it is also preferred that the liquid depolymerization product has a composition as suitable as possible for a cracker feed. This involves having a very low amount, or even the absence of a fraction with C28 or higher. Preferably, in the liquid depolymerization product, the amount of the fraction above C28 is equal to or lower than 4%, preferably lower than 3%, more preferably lower than 2%, relative to the total amount of liquid depolymerization product.

[0033] Furthermore, the quality of the cracker feed is higher when the depolymerized oil obtained from real plastic waste has low C6-C8 aromatics (Ar) values ​​and branching index (BI). The latter is defined as the molar ratio between internal double bonds relative to double bonds in chain end positions (alpha-olefins) as determined as described in the characterization section. Preferably, in the liquid depolymerization product, the branching index is lower than 0.5 wt%, more preferably lower than 0.4 wt%.

[0034] As used herein, "C6-C8 aromatic compounds" (Ar) refers to hydrocarbons having sigma bonds and delocalized pi electrons between carbon atoms forming a ring, wherein a total of 6 to 8 carbon atoms are present. Preferably, their amount entering the liquid depolymerization product is less than 1.3 wt%.

[0035] As already mentioned, the catalyst comprises a metal framework oxide (MOF).

[0036] MOFs are known to be highly porous crystalline materials made of organic linkers and inorganic blocks linked together in a textured structure. MOFs with either 3D (cage) or 2D (layered) framework types can be used as catalysts.

[0037] One of the MOF catalysts may be selected from the group consisting of: a MOF comprising a topology, such as a MOF having a zeolite topology, such as a zeolitic imidazolate framework (ZIF), a zeolite-like metal organic framework (ZMOF).

[0038] Another preferred group of MOF catalysts are MOF catalysts in which the organic linker is selected from the group consisting of carboxylate, phosphonate, N-based groups and NO-containing groups. Among them, carboxylate groups are preferred. Preferred carboxylate organic linkers are selected from fumaric acid carboxylate (FA), benzene-1,4-dicarboxylate (BDC), 1,3,5-benzenetricarboxylate (BTC), formic acid carboxylate.

[0039] Preferred MOFs belonging to this category are Zr-MOF-808 (BTC linker based on Zr), Ce-MOF-808 (BTC+FA linker based on Ce), MOF-199 (BTC linker based on Cu), MIL-88A (fumaric acid carboxylic acid ligand based on Fe2O3). Exemplary formulas of MOFs are Zr6O4(OH)4(-CO2)6(BTC)2(HCOO)6 for MOF-808; Zn4O(BDC)3 for MOF-5; and Cu3(C9H3O6)2 for MOF-199.

[0040] Additional exemplary MOFs can include, for example, the IRMOF series (MOF-5), the MOF-74 series, the Sandia metal-organic framework (SMOF) series, and the zeolitic imidazolate framework (ZIF) series.

[0041] An exemplary series of ZIFs include, but are not limited to, ZIF-4, ZIF-5, ZIF-6, ZIF-8, ZIF-10, and / or ZIF-11.

[0042] In some non-limiting embodiments, ZIF can have any useful topology defined by the same metal cation as the zeolite framework type SOD or RHO. SOD is a three-letter framework type code for the sodalite structure type, and RHO is another three-letter framework type code defined by the Structure Committee of the International Zeolite Association in "Atlas of zeolite framework types," Ch Baerlocher, LB McCusker, and DH Olson, Sixth Revised Edition, Elsevier Amsterdam, 2007. Examples are ZIF-4, ZIF-5, ZIF-8 (also known as ZIF-9, ZIF-10, ZIF-11, ZIF-12, ZIF-65, ZIF-67, ZIF-68, ZIF-69, ZIF-70, ZIF-71, ZIF-76, ZIF-78, ZIF-90, ZIF-95 and ZIF-100.

[0043] In another embodiment, the MOF (e.g., a crystalline MOF) can be a highly porous coordination framework, HKUST-1. The framework of HKUST-1 is [Cu3(benzene-1,3,5-carboxylic acid)2] or [Cu3(BTC)2], also known as MOF-199, Cu-BTC, and Basolite TM C300 (Sigma Aldric). It has interconnected [Cu2(O2CR)4] units (wherein R comprises an optionally substituted aromatic ring) which produce a three-dimensional system of channels in the solid with a pore size of 1 nm and an achievable porosity of about 40%.

[0044] In yet another embodiment, the MOF is MOF-5, which is Zn4O(1,4-phthalate)3.

[0045] The poison inhibitor may be used in combination with the catalyst. Preferably, it may be selected from the group consisting of Ca(OH)2, Mg(OH)2, Ba(OH)2, Sr(OH)2, CaO, Al2O3 and Zr(HPO4)2. Among them, Zr(HPO4)2 is preferably used.

[0046] The data reported in this disclosure demonstrate that the process according to the present disclosure allows the conversion of virgin resins as well as complex plastic wastes in liquid depolymerization products obtained in high yields and compositions making them suitable for use as cracker feedstocks.

[0047] Characterization

[0048] The properties were measured according to the following methods.

[0049] Analytical methods

[0050] Characterization of liquid products: by gas chromatography (GC) and proton NMR ( 1 The liquid products from both traps were characterized by H NMR.

[0051] GC analysis of the liquid product for each run was performed using an Agilent 7890 GC (Agilent Technologies, Santa Clara, CA) equipped with a standard nonpolar column and a flame ionization detector. <nC7、nC7<x<nC11、nC12<x<nC28、x> The weight percent of C28 is used to characterize the liquid product.

[0052] NMR data were used to characterize the percentage of aromatic, paraffinic, and olefinic protons in the liquid product. The examples were analyzed with the addition of CDCl3 (0.6 g of the depolymerized polymer / metal oxide mixture with 0.4 g CDCl3). Data were collected on a BrukerAV500 MHz NMR spectrometer (Bruker Corporation, Billerica, MA) at 25°C with a 5 mm Prodigy probe. One Dimension 1 H NMR data used The software (Bruker) was processed with an exponential line broadening window function. Quantitative measurements were performed with a 15 second relaxation delay, a 30° flip angle pulse, and 32 scans to facilitate accurate integration. Spectral integrations of aromatic olefin and paraffin protons were obtained and used to quantify the relative proportions of these protons.

[0053] Determination of Fe, Zr, Cu and Zn

[0054] The determination of the Fe, Zr, Cu and Zn content of the solid catalyst component is carried out by inductively coupled plasma emission spectrometry on an "ICP Spectrometer ARL Accuris" or on an "ICP Spectrometer Icap7000". The sample is prepared by weighing 0.1÷0.3 g of catalyst and 2 g of a 1 / 1 mixture of lithium metaborate / lithium tetraborate for analysis in a "Fluxy" platinum crucible. After adding a few drops of KI solution, the crucible is inserted in a special device "Claisse Fluxy" for complete combustion. The residue is collected with a 5% v / v HNO3 solution and then analyzed by ICP at the following wavelengths: iron, 259.94 nm / 261.187 nm; zirconium 349.62 nm / 343.82 nm; copper 327.40 nm; zinc 213.86 nm. Example

[0055] General depolymerization procedure

[0056] General procedure for depolymerization tests in 500 ml round glass reactors

[0057] 30 g of polymer plastic was loaded into a 500 mL round glass reactor with three necks equipped with a thermocouple and a nitrogen inlet. The polymer plastic can be virgin resin obtained directly from a polyolefin production facility (Examples 1-4 and Comparative Example 1) and a sample of real plastic waste (rpw) from a previously sorted municipal collection (Examples 5-7 and Comparative Examples 2-3).

[0058] Analysis of the actual plastic waste used in the examples showed that it consisted of about 97 wt% polyolefins with a PP / PE ratio of about 30 / 70), with the remainder containing trace amounts of other common polymers (PET, PS, PA, PU) plus inorganic contaminants.

[0059] An appropriate amount of solid catalyst (2.5 wt% relative to the plastic) was then introduced into the glass reactor. A blank test can also be performed without any catalyst. Two glass condensers were connected in series and maintained at 110°C and -8°C, respectively, using an oil bath (Cryostat Julabo). The reactor was placed in an electric heating system (blast furnace mantle bath) and the required power was set to raise the temperature to 450°C. The pyrolysis process occurred and the following experimental parameters were recorded:

[0060] L%, the sum of the yields of liquid condensable at 110°C + liquid condensable at -8°C (relative to the polymer charged)

[0061] S%, yield of solid / waxy residue in the reactor, excluding catalyst (relative to polymer charged)

[0062] G%, yield of non-condensable gaseous products in the two condensers (relative to the polymer charged)

[0063] The results are reported in Tables 1 and 2.

[0064] Comparative Example 1

[0065] Depolymerization runs were performed according to the general depolymerization procedure disclosed above using virgin polypropylene as the depolymerization feedstock and no depolymerization catalyst. The results are reported in Table 1.

[0066] Example 1

[0067] Preparation of MIL-88A

[0068] MIL-88A (Fe2O3-based fumaric acid carboxylic acid ligand) was prepared according to the procedure reported in Applied Catalysis B: Environmental 221 (2018), 119-128 and references cited therein. The obtained compound was characterized by X-ray analysis (figure consistent with literature data) and elemental analysis (Fe = 21.3 wt%).

[0069] The catalyst thus obtained was used in a depolymerization run according to the general depolymerization procedure disclosed above using virgin polypropylene as depolymerization feedstock. The results are reported in Table 1.

[0070] Example 2

[0071] Preparation of MOF 808

[0072] MOF808 (BTC linker based on Zr) was prepared according to the procedure reported in Material Letters 160 (2015), 412-414. The obtained compound was characterized by X-ray analysis (figure consistent with literature data) and elemental analysis (Zr = 19.0 wt%).

[0073] The catalyst thus obtained was used in a depolymerization run according to the general depolymerization procedure disclosed above using virgin polypropylene as depolymerization feedstock. The results are reported in Table 1.

[0074] Example 3

[0075] Preparation of MOF-199

[0076] MOF-199 (Cu-based BTC linker) was prepared according to the procedure reported in Tetrahedron 64 (2008), 8553-8557. The obtained compound was characterized by elemental analysis (Cu=17.6 wt%).

[0077] The catalyst thus obtained was used in a depolymerization run according to the general depolymerization procedure disclosed above using virgin polypropylene as depolymerization feedstock. The results are reported in Table 1.

[0078] Example 4

[0079] Preparation of MOF-5

[0080] MOF-5 (Zn-based terephthalic acid linker) was prepared according to the procedure reported in Tetrahedron 64 (2008), 8553-8557. A slight modification of the cited preparation provided that the dimethylformamide was first exchanged with ethanol in the work-up step, followed by the replacement of chloroform with acetone. The obtained compounds were characterized by elemental analysis.

[0081] The catalyst thus obtained was used in a depolymerization run according to the general depolymerization procedure disclosed above using virgin polypropylene as depolymerization feedstock. The results are reported in Table 1.

[0082] Comparative Example 2

[0083] Depolymerization runs were performed according to the general depolymerization procedure disclosed above, but using real plastic waste as depolymerization feedstock and no depolymerization catalyst. The results are reported in Table 2.

[0084] Example 5

[0085] The same catalyst used in Example 2 was used in a depolymerization run according to the general depolymerization procedure disclosed above, using real plastic waste as the depolymerization feedstock. In addition to the catalyst, Zr(HPO4)2 was used as a poison inhibitor (2.5 wt% relative to the plastic waste). The results are reported in Table 2.

[0086] Example 6

[0087] Preparation of MOF 808-Cerium doped

[0088] Ce-MOF-808-1.5-20FA was prepared according to the procedure reported in Microporous and Mesoporous Materials 324 (2021), 111303. The obtained compound was characterized by X-ray analysis (the spectrum was consistent with the literature data).

[0089] The catalyst thus obtained was used in a depolymerization run according to the general depolymerization procedure disclosed above, using real plastic waste as depolymerization feedstock. The results are reported in Table 2.

[0090] Example 7

[0091] The depolymerization run was performed as in Example 6, except that, in addition to the catalyst, Zr(HPO4)2 was used as a poison inhibitor (2.5 wt% relative to the plastic waste). The results are reported in Table 2.

[0092] Comparative Example 3

[0093] The depolymerization run was performed as in Example 5, except that zeolite HY was used instead of MOF-808. The results are reported in Table 2.

[0094] Table 1

[0095]

[0096] Table 2

[0097]

[0098] BI = Branching Index

[0099] Ar = aromatic compound content

Claims

1. A method for depolymerizing plastics, comprising the following steps: a) providing a molten plastic waste feedstock comprising at least recycled polypropylene, and b) subjecting the molten product obtained in (a) to a temperature ranging from 280° C. to 600° C. to obtain a depolymerized product; The method is characterized by the fact that either or both of the molten product and the depolymerized product are contacted with a metal organic framework catalyst.

2. The method according to claim 1, wherein the amount of the catalyst ranges from 0.1 to 20 wt%, preferably from 0.1 to 10 wt%, especially from 0.1 to 5 wt%, relative to the total weight of the plastic waste feedstock and the catalyst.

3. The method according to one or more of the preceding claims, wherein the plastic waste feedstock comprises a mixture of polyethylene and polypropylene in a weight ratio of 85:15 to 15:85, more preferably 80:20 to 20:

80.

4. The method according to one or more of the preceding claims, wherein the MOF has a 3D (cage) framework.

5. The method according to one or more of the preceding claims, wherein the MOF has a 2D (hierarchical) framework.

6. The method according to one or more of the preceding claims, wherein the MOF catalyst is selected from the group consisting of: a MOF having a zeolite topology.

7. The method according to one or more of the preceding claims, wherein the organic linker of the MOF is selected from the group consisting of carboxylates, phosphonates, N-based groups and NO-containing groups.

8. The method according to claim 7, wherein the organic linker is selected from fumaric acid carboxylate (FA), benzene-1,4-dicarboxylate (BDC), 1,3,5-benzenetricarboxylate (BTC), formic acid carboxylate.

9. The method according to claim 8, wherein the MOF is selected from the group consisting of: Zr-MOF-808 (BTC linker based on Zr), Ce-MOF-808 (BTC+FA linker based on Ce), MOF-199 (BTC linker based on Cu), MIL-88A (fumaric acid carboxylic acid ligand based on Fe2O3).

10. The method according to one or more of the preceding claims, wherein the MOF is MOF-5 based on Zn4O(1,4-phthalate)3.

11. The method according to one or more of the preceding claims, wherein the MOF is used in combination with a poison inhibitor.

12. The method of claim 11, wherein the poison inhibitor is selected from the group consisting of Ca(OH)2, Mg(OH)2, Ba(OH)2, Sr(OH)2, CaO, Al2O3, and Zr(HPO4)2.

13. The process of claim 1, wherein the amount of liquid depolymerization product is greater than 60 wt% of the initially fed plastic waste feedstock.

14. Process according to one or more of the preceding claims, wherein the amount of fractions higher than C28 in the liquid depolymerization product is equal to or lower than 4%, relative to the total amount of liquid depolymerization product.

15. Process according to one or more of the preceding claims, wherein the branching index of the liquid depolymerization product does not exceed 1 wt.-%.

Citation Information

Cited By

  • Polycarbonate depolymerization method based on solvent-mof composite catalytic system

    CN122854036A